1990
DOI: 10.1093/carcin/11.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke condensate and 12-0-tetradecanoylphorbol-13-acetage on gap junction structure and function in cultured cells

Abstract: The effects of cigarette smoke condensate (CSC) and the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA) on gap junction structure, quantity and function were investigated. Gap junction morphology was studied in rotary-shadowed freeze-fracture replicas of primary chick embryo hepatocytes. CSC (24 micrograms/ml) induced a strong decrease of gap junction areas; within 6 h the areas were reduced by greater than 60%. In the first 3 h of exposure, TPA (100 ng/ml) also reduced gap junction areas, but in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A more sophisticated approach is the local liberation of inositol triphosphate from a caged precursor by flash photolysis, which allows the stimulation of single cells (Decrock et al, 2015; Leybaert and Sanderson, 2001). Metabolic coupling assays, in particular transfer of labelled nucleotides, have been used to demonstrate the inhibitory effects of 12- O -tetradecanoylphorbol-13-acetate on GJIC in co-cultures of primary chick embryo hepatocytes and Chinese hamster V79 lung fibroblasts (van der Zandt et al, 1990).…”
Section: In Vitro Methods To Study Liver Gap Junctionsmentioning
confidence: 99%
“…A more sophisticated approach is the local liberation of inositol triphosphate from a caged precursor by flash photolysis, which allows the stimulation of single cells (Decrock et al, 2015; Leybaert and Sanderson, 2001). Metabolic coupling assays, in particular transfer of labelled nucleotides, have been used to demonstrate the inhibitory effects of 12- O -tetradecanoylphorbol-13-acetate on GJIC in co-cultures of primary chick embryo hepatocytes and Chinese hamster V79 lung fibroblasts (van der Zandt et al, 1990).…”
Section: In Vitro Methods To Study Liver Gap Junctionsmentioning
confidence: 99%
“…Phosphorylation of Cx43 at multiple c-terminal amino acid residues such as Ser-279/282, Tyr-265, Ser-368, and Ser-262 are targeted by the aforementioned signaling pathways, and have been described as inhibitory phosphorylations (Lampe and Lau 2000). The phorbol ester, PMA (phorbol myristic acid), is commonly used as a receptor-independent inhibitor of gap junction function (Lampe 1994; Sirnes, et al 2008; van der Zandt, et al 1990) and signals through PKC, Src, and ERK in UAEC (Bird et al 2013). Indeed, when P-UAEC are exposed to PMA, sustained phase Ca2+ burst responses to ATP are dramatically reduced (Bird et al 2013; Cale and Bird 2006), and this is associated with the phosphorylation of Cx43 at both positions Ser-279/282 via the ERK-1/2 pathway and Tyr-265 via the Src pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory effect on IC of cigarette smoke condensate (CSC) is not transient (Jongen et al 1987;Rutten et al 1989;Van Der Zandt et al 1990). In addition, TPA, but not CSC, has been shown to reduce the number of gap junctions in V79 cells (Jongen et al 1987;Van Der Zandt et al 1990) and it has recently been shown that these compounds induce different effects on gap junction morphology and quantity (Van Der Zandt et al 1990). CSC does not seem to activate PKC ( Van der Zandt et al 1990), and this suggests that these compounds act via different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TPA, but not CSC, has been shown to reduce the number of gap junctions in V79 cells (Jongen et al 1987;Van Der Zandt et al 1990) and it has recently been shown that these compounds induce different effects on gap junction morphology and quantity (Van Der Zandt et al 1990). CSC does not seem to activate PKC ( Van der Zandt et al 1990), and this suggests that these compounds act via different mechanisms. The mechanism by which APM inhibits IC and the compounds responsible for this inhibition are unknown.…”
Section: Discussionmentioning
confidence: 99%